2020
DOI: 10.1080/07420528.2020.1772809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altered photoperiod due to COVID-19 lockdown on pregnant women and their fetuses

Abstract: Maternal circadian rhythms provide highly important input into the entrainment and programming of fetal and newborn circadian rhythms. The light-dark cycle is an important regulator of the internal biological clock. Even though pregnant women spend a greater part of the day at home during the latter stages of pregnancy, natural light exposure is crucial for the fetus. The current recommended COVID-19 lockdown might dramatically alter normal environmental lighting conditions of pregnant women, resulting in expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 130 publications
(156 reference statements)
0
17
0
Order By: Relevance
“…Further studies needed to explore the underlying reasons led to the skip of regular check-ups. In addition, one study also suggested the lockdown policy may interfere with the circadian rhythm of women and fetuses, which may have led to several adverse pregnancy outcomes and may result in CS [27]. These results advocate that more medical support and more targeted guidance should be implemented in severely affected regions.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies needed to explore the underlying reasons led to the skip of regular check-ups. In addition, one study also suggested the lockdown policy may interfere with the circadian rhythm of women and fetuses, which may have led to several adverse pregnancy outcomes and may result in CS [27]. These results advocate that more medical support and more targeted guidance should be implemented in severely affected regions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculated that anxiety or other factors during the lockdown made the maternal diet style change, resulting in excessive nutrient transport to the fetus and placenta which further leading to fetal macrosomia. Studies have found that moderate exercise is helpful to improve GDM condition, especially bene ting from walking [27][28][29]. The light regulation of circadian rhythm has also been found to be essential for fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, chronic changes during the daytime photoperiod are enhanced by artificial light during nighttime [8]. Change in photoperiod, as indicated by the longtime light exposure which occurred in lockdown during Covid-19, may alter the function of all body organs, according to Bagic et al [13]. However, several questions are arising in this regard.…”
Section: The Impact Of Covid-19 Lockdown On Circadian Rhythmmentioning
confidence: 94%
“…There are scanty studies concerning the effects of lockdown on change in circadian rhythm and its hazardous effects on metabolic status. However, in one study, Bagci and colleagues (2020) have emphasized that chronic photoperiod change during lockdown may dramatically affect different organs of the fetus body during its development [13]. According to the previous studies, chronic changes during the daytime photoperiod are enhanced by artificial light during nighttime [8].…”
Section: The Impact Of Covid-19 Lockdown On Circadian Rhythmmentioning
confidence: 99%